Proprioceptive Localization of the Hand Changes When Skin Stretch around the Elbow Is Manipulated - Kuling, Irene A.; Brenner, Eli; Smeets, Jeroen B. J. (Frontiers in Psychology, 2016)
Cutaneous information has been shown to influence proprioceptive position sense when subjects had to judge or match the posture of their limbs. In the present study, we tested whether cutaneous information also affects proprioceptive localization of the hand when moving it to a target. In an explorative study, we manipulated the skin stretch around the elbow by attaching elastic sports tape to one side of the arm. Subjects were asked to move the unseen manipulated arm to visually presented targets. We found that the tape induced a significant shift of the end-points of these hand movements. Surprisingly, this shift corresponded with an increase in elbow extension, irrespective of the side of the arm that was taped. A control experiment showed that this cannot be explained by how the skin stretches, because the skin near the elbow stretches to a similar extent on the inside and outside of the arm when the elbow angle increases and decreases, respectively. A second control experiment reproduced and extended the results of the main experiment for tape on the inside of the arm, and showed that the asymmetry was not just a consequence of the tape originally being applied slightly differently to the outside of the arm. However, the way in which the tape was applied does appear to matter, because applying the tape in the same way to the outside of the arm as to the inside of the arm influenced different subjects quite differently, suggesting that the relationship between skin stretch and sensed limb posture is quite complex. We conclude that the way the skin is stretched during a goal-directed movement provides information that helps guide the hand towards the target.